2017
DOI: 10.3390/f8060186
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Habitat Elements and Their Distribution over Several Spatial Scales: The Case of the Fisher

Abstract: Abstract:In past studies of the fisher (Pekania pennanti) most researchers have concluded that fisher habitat must consist of mostly mature to late-seral forest with few, if any, openings. Without doubt, certain elements found in mature to late-seral forests are required by females to successfully rear their young, but some recent work casts doubt on the extent that a continuous canopy of tree coverage and a preponderance of older stands are necessary as long as certain components exist. This paper explores th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Finally, foraging fishers may be more tolerant of forest openings and heterogeneity from past management than expected, and willing to trade the risk of using more open canopy for the increase in prey associated with the greater ground cover and understory of early successional stands [ 75 ]. Smith [ 86 ] found that fishers in Oregon continued to use recently thinned habitat in their home ranges given that sufficient den sites and canopy cover > 50% was maintained within 2 km in the home range, Green et al [ 87 ] showed that fishers translocated to an area in the Sierra Nevada of California with high levels of current and historical forest management survived and increased in abundance over 7 years of monitoring, and Niblett et al [ 88 ] found that fisher home ranges in California could contain up to 25% of open canopy provided that enough large trees for den locations were present.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, foraging fishers may be more tolerant of forest openings and heterogeneity from past management than expected, and willing to trade the risk of using more open canopy for the increase in prey associated with the greater ground cover and understory of early successional stands [ 75 ]. Smith [ 86 ] found that fishers in Oregon continued to use recently thinned habitat in their home ranges given that sufficient den sites and canopy cover > 50% was maintained within 2 km in the home range, Green et al [ 87 ] showed that fishers translocated to an area in the Sierra Nevada of California with high levels of current and historical forest management survived and increased in abundance over 7 years of monitoring, and Niblett et al [ 88 ] found that fisher home ranges in California could contain up to 25% of open canopy provided that enough large trees for den locations were present.…”
Section: Discussionmentioning
confidence: 99%
“…The kernel function is based on the quartic kernel function described in [61]. This method finds application in many fields of science, such as: archaeology [65,66], astronomy [67][68][69][70][71], biology [72][73][74][75], forecasting [76,77], environmental protection [78,79], medicine and health studies [80][81][82][83], and many others. Choosing the appropriate bandwidth in KDE is the subject of many studies [84][85][86].…”
Section: Methodsmentioning
confidence: 99%